2018
DOI: 10.1002/2017jd027472
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating InSAR Maps of Water Vapor to Improve Heavy Rainfall Forecasts: A Case Study With Two Successive Storms

Abstract: Very high resolution precipitable water vapor maps obtained by the Sentinel‐1 A synthetic aperture radar (SAR), using the SAR interferometry (InSAR) technique, are here shown to have a positive impact on the performance of severe weather forecasts. A case study of deep convection which affected the city of Adra, Spain, on 6–7 September 2015, is successfully forecasted by the Weather Research and Forecasting model initialized with InSAR data assimilated by the three‐dimensional variational technique, with impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“…These results show a strong case for the assimilation of InSAR data in weather forecasts, bolstering a few specific case studies of some severe deep‐convection events (Mateus et al, ). The relatively large sample of cases evaluated here suggests that such gains were not fortuitous, but a consistent response to an improved initial state, valid in different weather conditions.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results show a strong case for the assimilation of InSAR data in weather forecasts, bolstering a few specific case studies of some severe deep‐convection events (Mateus et al, ). The relatively large sample of cases evaluated here suggests that such gains were not fortuitous, but a consistent response to an improved initial state, valid in different weather conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Mateus et al () showed a significant improvement in the atmospheric moisture content and on the formation of light precipitation up to 9 hr after the assimilation time in a 3D‐Var data assimilation experiment using InSAR‐PWV maps, estimated from the ENVISAT‐ASAR data, and the Weather Research and Forecast (WRF) model over Lisbon, Portugal. Mateus et al () showed that in a case with two successive deep convection storms, which could be both well forecasted only after InSAR data assimilation, using two PWV maps estimated from new generation SAR images obtained by Sentinel‐1 A over Adra, Spain, with the 3D‐Var method and the WRF model. The latter result suggested the high potential added value of the new InSAR data, and the need for a systematic evaluation of its value in a representative range of weather conditions, which is the objective of the current study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After compensation of the tropospheric differential phases, the height-dependent phase has been significantly mitigated (see right column of Figure 9). Other atmospheric effects with lower magnitude are thus visible, such as the turbulent atmosphere, which is not contained in the ECMWF data but could be potentially modeled using meso-scale weather assimilation techniques [49,50].…”
Section: Remote Sensing Technologymentioning
confidence: 99%
“…The spatial and temporal rapid variations of the tropospheric water vapor in the low atmosphere poses one of the main challenges to the numerical weather models (NWMs) forecast accuracy [1]. Nowadays, the atmospheric measurement techniques are still insufficient to measure the tropospheric water vapor with the temporal and spatial resolution needed for the NWM precise forecasts [2]. The model's uncertainty regarding the water vapor distribution limits its capability to identify instability situations, which can trigger heavy rain occurrences [3].…”
Section: Introductionmentioning
confidence: 99%